SOCIAL CRITIQUE IN MERDEKA SHORT STORY BY PUTU WIJAYA: A DYSTOPIAN LITERATURE APPROACH - Manugeren, M; Purwarno, Purwarno; Siwi, Purwanto; Ekalestari, Susi; Wulan, Sri (University of Kuningan, 2022)
Changes in a society produce social critiques which in turn become a means of communicating new ideas in addition to assessing old ideas for social change, in short as a vehicle for the conservation and reproduction of a social system. Social critique can be conveyed through literary works; this is seen from the short story of Merdeka by Putu Wijaya. Through a dystopian literary approach and supported by related theories and concepts, it is revealed that this short story is full of social critiques as a result of the author's observations of his environment. The flow of dystopia is generally speculative, presenting a catastrophic or chaotic landscape of the future civilization of the world. Dystopian literature is always associated with socio-political discourse. Overall this research is carried out using a qualitative descriptive method with the aim of presenting a complete picture of the social setting and clarification of social phenomena in the short story of Merdeka and then synchronizing it with social reality. The results show that the forms of social critique conveyed by the author is lack of self-introspection, social gap and environmental damage. These three forms of social critique if uncontrolled can cause chaos in the social system because the main result is conflict, the color of dystopian literature.